RETRACTED: Analysis of mechanical impurities contained in pumped liquids at the fields of Western Siberia - Pogrebnaya Irina; Mikhailova Svetlana (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001